Methodology for Developing Cultural Thinking in Teachers Through the Analysis of Artworks - Muzropova Guljamol Mardonovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: The article examines methodologies for developing cultural thinking in teachers through the analysis of artworks. It highlights pedagogical approaches and practical techniques that enable educators to interpret, evaluate, and reflect on artistic works while fostering cultural awareness and aesthetic understanding. The study emphasizes that systematic analysis of art enhances teachers’ ability to integrate cultural knowledge into their teaching practices, promoting intercultural competence and critical thinking.